2023
DOI: 10.3390/ijms24119773
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Striatal Dopamine Transporter Availability and Heightened Response to Natural and Pharmacological Stimulation in CCK-1R-Deficient Obese Rats

Abstract: Alterations in dopamine neurotransmission are associated with obesity and food preferences. Otsuka Long-Evans Tokushima Fatty (OLETF) rats that lack functional cholecystokinin receptor type-1 (CCK-1R), due to a natural mutation, exhibit impaired satiation, are hyperphagic, and become obese. In addition, compared to lean control Long-Evans Tokushima (LETO) rats, OLETF rats have pronounced avidity for over-consuming palatable sweet solutions, have greater dopamine release to psychostimulants, reduced dopamine 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
1
1
0
Order By: Relevance
“…It has been well-described that the activation of GLP-1 receptors in the NTS contributes to food reward-suppressing behaviors through targeting mesolimbic dopamine [161,256]. Similar findings have been observed in the striatum following the activation of the Y2 receptor by PYY [257], as well as CCK receptor activation, with CCK-1R-deficient obese rats displaying reduced basal dopamine transmission [240]. Interestingly, several studies have shown that SG-induced increases in Clostridia may initiate changes in the striatum to improve GLP-1 release [258].…”
Section: Bariatric Surgery Gut Microbiota Dopamine and Gut Hormonessupporting
confidence: 69%
See 1 more Smart Citation
“…It has been well-described that the activation of GLP-1 receptors in the NTS contributes to food reward-suppressing behaviors through targeting mesolimbic dopamine [161,256]. Similar findings have been observed in the striatum following the activation of the Y2 receptor by PYY [257], as well as CCK receptor activation, with CCK-1R-deficient obese rats displaying reduced basal dopamine transmission [240]. Interestingly, several studies have shown that SG-induced increases in Clostridia may initiate changes in the striatum to improve GLP-1 release [258].…”
Section: Bariatric Surgery Gut Microbiota Dopamine and Gut Hormonessupporting
confidence: 69%
“…DAT packages extracellular dopamine into synaptic vesicles so that dopamine may be re-released into the synaptic cleft [158]. In obesity, DAT binding is reduced in the striatum [232]; therefore, less dopamine is available within synaptic clefts during palatable food consumption [240]. As discussed above, our previous work showed that RYGB in the fat-diet-induced obese rat model restored blunted DAT availability [232].…”
Section: Bariatric Surgery Gut Microbiota Mesolimbic Pathway and Stri...mentioning
confidence: 87%